2021
DOI: 10.1038/s41467-021-23474-5
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation of MLKL at lysine 219 positively regulates necroptosis-induced tissue injury and pathogen clearance

Abstract: Necroptosis is a lytic, inflammatory form of cell death that not only contributes to pathogen clearance but can also lead to disease pathogenesis. Necroptosis is triggered by RIPK3-mediated phosphorylation of MLKL, which is thought to initiate MLKL oligomerisation, membrane translocation and membrane rupture, although the precise mechanism is incompletely understood. Here, we show that K63-linked ubiquitin chains are attached to MLKL during necroptosis and that ubiquitylation of MLKL at K219 significantly cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 69 publications
0
43
0
Order By: Relevance
“…According to a recently published study, mouse MLKL is also ubiquitinated at lysine 219, and it was suggested that this ubiquitination, as well as ubiquitination of the corresponding lysine residue in human MLKL (at position 230), serve to facilitate death induction [ 28 ]. However, in our repeated mass spectroscopy analysis we could not discern ubiquitination of lysine 230 in HT-29 cells that had been treated for 3 h with TBZ.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recently published study, mouse MLKL is also ubiquitinated at lysine 219, and it was suggested that this ubiquitination, as well as ubiquitination of the corresponding lysine residue in human MLKL (at position 230), serve to facilitate death induction [ 28 ]. However, in our repeated mass spectroscopy analysis we could not discern ubiquitination of lysine 230 in HT-29 cells that had been treated for 3 h with TBZ.…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry identified K219 as a ubiquitination site of mouse MLKL and mutation of the site was shown to reduce K63-linked ubiquitination of MLKL, generated during TNF-α-induced necroptosis [ 119 ]. Additionally, ubiquitinated K219 was shown to predominantly promote necroptosis in mouse dermal fibroblasts (MDFs) derived from Mlkl K219R/K219R knock-in mice, which almost completely blocked TNF-α-induced necroptosis, and abrogated phenotypes associated with necroptosis-induced tissue injury were seen in Mlkl K219R/K219R mice [ 119 ]. Interestingly, Mlkl K219R/K219R MDFs cannot form nearly as many higher-order MLKL polymers in membrane fractions compared to wild-type MDFs, indicating that K219 ubiquitination promotes MLKL oligomerisation at the plasma membrane [ 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ubiquitinated K219 was shown to predominantly promote necroptosis in mouse dermal fibroblasts (MDFs) derived from Mlkl K219R/K219R knock-in mice, which almost completely blocked TNF-α-induced necroptosis, and abrogated phenotypes associated with necroptosis-induced tissue injury were seen in Mlkl K219R/K219R mice [ 119 ]. Interestingly, Mlkl K219R/K219R MDFs cannot form nearly as many higher-order MLKL polymers in membrane fractions compared to wild-type MDFs, indicating that K219 ubiquitination promotes MLKL oligomerisation at the plasma membrane [ 119 ]. In contrast, another study showed that exogenous expression of a non-ubiquitinated MLKL-USP21 fusion protein (USP21 removes all Ub conjugates from a protein) had minimal effects on TNF-α-induced necroptosis, but did affect MLKL stability [ 120 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylated MLKL undergoes conformational changes and disengagements from RIPK3; then, the MLKL oligomer is transferred to the cell membrane, leading to cell expansion and rupture ( Wang H. et al, 2014 ; Garnish et al, 2021 ). Recently, it has been found that MLKL ubiquitination is also correlated with MLKL activation and necroptosis, and MLKL ubiquitination at K219 imposes the cytotoxic potential of phosphorylated MLKL ( Garcia et al, 2021 ). Cell rupture is followed by the release of a large number of endogenous host-derived molecules such as adenosine triphosphate, IL-33, heat-shock proteins, and high-mobility group box 1 (HMGB1) and other DAMPs, thus causing an excessive inflammatory response and aggravating surrounding tissue damage ( Scaffidi et al, 2002 ; Iyer et al, 2009 ; Gong et al, 2020 ).…”
Section: The Mechanism Of Necroptosis and Its Relationship With Apoptosismentioning
confidence: 99%